2001
DOI: 10.4141/p01-006
|View full text |Cite
|
Sign up to set email alerts
|

Response of pea to rhizobia inoculation and starter nitrogen in Alberta

Abstract: 2001. Response of pea to rhizobia inoculation and starter nitrogen in Alberta. Can. J. Plant Sci. 81: 637-643. The introduction of new semileafless cultivars has contributed to the rapid expansion of pea (Pisum sativum) on the Canadian prairies. To determine the response of four new semi-leafless cultivars to rhizobia inoculation and starter fertilizer N, 58 field trials were conducted from 1995 to 1998 over a wide geographic region of Alberta. However, due to possible cross-contamination in 1995 and 1996 betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…Consequently, field pea was grown under a high N environment, particularly, Fort Vermilion in 1996. McKenzie et al (2001) reported that in 22 trials conducted in Alberta, the level of soil NO 3 -N prior to planting did not affect the frequency of inoculation benefits to pea yield. Indeed, as many as 50% of the trials with spring soil NO 3 -N levels greater than 40 kg ha -1 responded to rhizobia inoculation, suggesting that field pea nodulation and N 2 fixation may not be highly sensitive to residual soil inorganic N levels.…”
Section: Nodulationmentioning
confidence: 98%
“…Consequently, field pea was grown under a high N environment, particularly, Fort Vermilion in 1996. McKenzie et al (2001) reported that in 22 trials conducted in Alberta, the level of soil NO 3 -N prior to planting did not affect the frequency of inoculation benefits to pea yield. Indeed, as many as 50% of the trials with spring soil NO 3 -N levels greater than 40 kg ha -1 responded to rhizobia inoculation, suggesting that field pea nodulation and N 2 fixation may not be highly sensitive to residual soil inorganic N levels.…”
Section: Nodulationmentioning
confidence: 98%
“…However, the site effects on the inoculant performance observed in the present study might also be related to other factors such as soil attributes and environmental conditions. Pre-seeding available soil N in the 0-to 60-cm depth was greater at Stewart Valley (17 kg ha -1 ) than at Swift Current (13 kg ha -1 ), but residual soil NO 3 -N usually does not appreciably affect the frequency of inoculation benefits (McKenzie et al 2001). Clayton et al (2004b) observed that at an available soil NO 3 -N level of 40 kg ha -1 , dry pea still had good responses to inoculation, suggesting that annual pulses may not be sensitive to available soil NO 3 -N in terms of nodule formation and nitrogen fixation.…”
Section: Seed Yieldmentioning
confidence: 99%
“…An alternative is to apply the inoculant to the soil at the time of planting. Soil inoculation with a granular form has been successful for faba bean (Vicia faba L.) (Dean and Clark 1977), soybean (Glycine max L.) (Danso et al 1990), field pea (Pisum sativum L.) (McKenzie et al 2001;Clayton et al 2004a), and chickpea (Kyei-Boahen et al 2002). However, no information is available on the response of chickpea to placement of granular inoculants in the soil.…”
mentioning
confidence: 99%
“…Carneval was one of the highest yielding cultivars in tests conducted across Alberta (McKenzie et al 2001a). Trials were planted at recommended rates to provide approximately 80 plants m -2 .…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of water use and ET efficiency were components of field trials conducted to evaluate the effect of cultivar, rhizobia inoculation and fertilizer on pea seed yield across all agro-ecological regions of Alberta (McKenzie et al 2001a, b). Sites for this study were all located in the Dark Brown and Black soil zones except one irrigated site located in the Brown soil zone (Table 1).…”
Section: Methodsmentioning
confidence: 99%